2. STUDY ON CARDIOVASCULAR RISK LEVELS AND RELATED FACTORS AMONG TYPE 2 DIABETES INPATIENTS AT LONG XUYEN CITY HEALTH CENTER IN 2024 (Vietnam Journal of Community Medicine, 2025)
Background: The risk of cardiovascular damage in type 2 diabetes patients increases 2-4 times compared to normal individuals, and protective factors against atherosclerotic cardiovascular disease are completely lost in diabetic patients. Studying the levels of cardiovascular risk in diabetic patients is extremely necessary to help control cardiovascular risk factors early and actively, contributing to slowing the progression of the disease, helping to reduce complications and improve the quality of life for patients, thereby reducing the burden of medical costs for society.Objectives: To determine the proportion levels of cardiovascular risk and analyze some factors related to the level of cardiovascular risk in type 2 diabetes patients receiving inpatient treatment at Long Xuyen city Health Center in 2024.Materials and methods: A cross-sectional descriptive study with analysis was conducted on 124 type 2 diabetes inpatients at Long Xuyen city Health Center.Results: The very high cardiovascular risk accounted for 88.7%, the high cardiovascular risk 3.2%, and the average cardiovascular risk 8.1%. Factors related to cardiovascular risk: age, BMI, and waist circumference.Conclusion: The rate of patients with very high cardiovascular risk is quite high, thus attention should be paid to glycemic control treatment, especially in patients over 60 years old, with 10 years or more of diabetes, and obese patients. It is essential to recommend to type 2 diabetes patients regarding lifestyle behaviors such as smoking, sedentary lifestyle, and non-compliance with treatment, as these factors can elevate the risk of cardiovascular disease.
Keywords: Type 2 diabetes; cardiovascular disease; cardiovascular risk levels.